Faktor yang Mempengaruhi Kemampuan Komunikasi Ekspresif Anak Tunagrahita: Studi Kasus Azka A.P di SLB Al Azhar Medan (International Forum of Researchers and Lecturers, 2025)
This research aims to analyze the factors that influence the tendency of children with intellectual disabilities to develop expressive communication skills. Expressive communication skills, which include speaking and verbally expressing needs, are an important aspect of development for children with intellectual disabilities to adapt in social environments. The research method uses a qualitative approach with a case study technique on a student with mild intellectual disability named Azka Ari Pratama (10 years old) at SLB Al Azhar Medan. Data collection was carried out through participant observation, semi-structured interviews with teachers, and direct observation. The results of the research indicate that expressive communication skills are influenced by individual factors (intellectual limitations and emotional regulation), physiological factors, environmental factors, and motivational factors. The research concludes that a holistic and individualized approach is needed in the development of expressive communication of children with intellectual disabilities, considering all identified factors.